A new species and two new records of Quercus (Fagaceae) from northern Vietnam - Hoàng, Thị Bình (2023)
A new species, Quercus xuanlienensis Binh, Ngoc & Bon, is described from Xuan Lien Nature Reserve, Vietnam. The new species is morphologically similar to Q. edithiae Skan, in having 8–11 pairs of secondary veins, bowl-shaped cupules and ellipsoid to cylindrical-ellipsoid and basally convex nuts. It differs in having serrulate leaf margins only at apical 1/5–1/7, almost entire margins of bracts on cupule and much longer nuts. The species is also similar to Q. fleuryi Hickel & A. Camus in having leaves glabrous on both surfaces with only an apically serrulate margin but differs in having shorter petioles, cupules enclosing 1/5 of the nut and much longer nuts. In addition, Q. disciformis Chun & Tsiang. and Q. bella Chun & Tsiang., previously known from China, are newly recorded from Ba Vi National Park, Vietnam.